Genetic variability, heritability and yield components of waterlogging-tolerant hybrid maize. Issue 1 (February 2021) - Muliadi, A; Effendi, R; Azrai, M
Abstract: Waterlogging is one of the abiotic stresses which can be one of the most important constraints for maize production. The objective of this study is to estimate genetic variability, heritability, correlations for grain yield and yield component of waterlogging-tolerant maize. This research was conducted in two locations, laid out in a randomized complete block design with three replications. The research material consisted of 8 hybrids and 2 check varieties. The L19/MR14 hybrids had the highest grain yield (9.64 t ha −1 ), followed by L15/MR14 hybrids (9.30 t ha −1 ) and L12/MR14 (9.20 t ha −1 ). Genotypic variants ranged from 0.00 to 15.98, while phenotypic variants ranged from 0.06 to 20.43. Broad sense heritability estimates were moderately high for days to 50% silking, thousand kernel weight, ear length, number of kernel rows per ear. The characters observed generally showed a positive correlation with grain yield, except for plant height and ear height. The thousand kernel weight has a positive and large direct effect on the grain yield and it is almost the same as the correlation value. Therefore, the character could be considered as important selection criteria for grain yield improvement of waterlogging tolerant maize breeding program.